Perjanjian Indonesia Dengan Palestina - Juan Perdana; Sri Ulina Br. Pinem; Tamaulina Br.Sembiring (Jurnal Multidisiplin Indonesia, 2024)
The international cooperation agreement between Indonesia and Palestine, which was formalized by Presidential Regulation Number 34 of 2018, is an important milestone in bilateral relations between the two countries. This agreement is based on long-standing close and close relations, where Indonesia consistently supports the Palestinian struggle for independence and rejects recognition of Israel until a just two-state solution is achieved. This agreement is primordial in enhancing friendly and fraternal relations, and has the main objective of strengthening economic and trade cooperation between the two countries. The results of this agreement include improving social life and economic independence for Palestine through the policy of eliminating import duties for certain products from Palestine. Further analysis shows that this agreement has the potential to provide economic benefits for Palestine, which can facilitate private sector development and job creation, while also having a positive impact on Indonesia in the form of access to unique products of Palestinian origin. The conclusion drawn from this discussion is that this agreement not only strengthens diplomatic relations, but also supports Palestinian social and economic progress, in line with the principles of international solidarity and support for Palestinian independence and sovereignty.